Treatment Effects of Acupuncture and Calligraphy Training on Cognitive Abilities in Senile Demented Patients - Henry S. R Kao; Miqu Wang; Shuguang Yu; Shihong Yuan; Miranda M. Y Fung; Lin Zhu; Stewart P. W Lam; Tin Tin Kao; Xiaoyang Kao (Wolters Kluwer Health/LWW, 2019)
Purpose: This study compared the relative effectiveness of Chinese calligraphy handwriting (CCH) and acupuncture in the treatment of patients with senile dementia. Materials and Methods: A randomized controlled trial (RCT) with 17 mild-to-moderate dementia patients with an average age of 77.29 years were randomly assigned with 9 to the calligraphy handwriting group and 8 to the acupuncture treatment group for a month of consecutive treatment. The participants' cognitive abilities, as well as symptoms of senile dementia, were measured by the Chinese version of the Mini-mental State Examination (CMMSE) and the Chinese Medicine Quantitative Diagnostic Survey for Senile Dementia Symptoms, respectively, before and after the treatment. Results: The calligraphy group showed a significant increase in calculation and memory as well as a decline in the symptoms of senile dementia. Patients in the acupuncture group experienced a significant growth in total CMMSE scores and the subscales in orientation to time and place, behavioral operations, as well as reduced clinical symptoms. However, no significant changes were found in their memory and calculation abilities. Conclusion: Both CCH and acupuncture treatments were found significantly effective for, respectively, enhancing the patients' cognitive abilities and reducing their clinical symptoms. Further, calligraphy handwriting also improved the level of their attention and concentration, physical relaxation, and emotional stability.